مفهوم القرار الإداري السلبي في الفقه والقضاء الإداري - محمد عمر الجداع (Aljameai, 1970)
المستخلص:يُعد القرار الإداري من أهم الوسائل القانونية التي عن طريقها تستطيع الإدارة التعبير عن إرادتها، وتتنوع هذه القرارات إلى أشكال كثيرة، فكما يمكن أن يكون القرار الإداري صريحاً يمكن أن يكون ضمنياً، وقد يكون القرار الإداري إيجابياً أو سلبياً بإلتزام الإدارة الصمت تجاه موقف معين.وإذا كان الأصل أن الإدارة تعبر عن إرادتها في صورة قرارات مكتوبة تفصح من خلالها عن رغبتها في إحداث أثر قانوني معين، إلا أنها أحياناً تلتزم جانب الصمت تجاه موقف معين بالرغم من أنها ملزمة وفقاً للقانون بإتخاذ إجراء، مما قد يؤدي هذا الصمت أو السكوت إلى ضرر لأصحاب المصلحة يرتب مسؤوليتها الإدارية.ولإقامة التوازن بين المصلحة العامة ومصلحة الأفراد، فقد تدخل المشرع وقرر أن صمت الإدارة وعدم الرد أو إتخاذ موقف صريح بمثابة قرار إداري سلبي يجوز الطعن فيه أمام القضاء. من ذلك ما نصت عليه المادة الثانية من القانون رقم (88) لسنة 1971ميلادي، بشأن القضاء الإداري: (يعتبر في حكم القرارات الإدارية رفض السلطات الإدارية أو امتناعها عن إتخاذ قرار أو إجراء كان من الواجب عليها إتخاذه وفقاً للقوانين واللوائح).لذلك فإن القرار الإداري السلبي يكمن في رفض الإدارة أو إمتناعها عن إتخاذ قرار كان من الواجب عليها إتخاذه بحكم القانون، وهو يرتبط بالتصرفات الصادرة عن الإدارة وهي تمارس سلطتها المقيدة.Abstract:The administrative decision is considered one of the most important legal means through which the administration can express its will, and these decisions vary in many forms. Just as the administrative decision can be explicit, it can be implicit, and the administrative decision may be positive or negative, with the administration remaining silent about a particular situation.And if the principle is that the administration expresses its will in the form of written decisions through which it expresses its desire to bring about a certain legal effect, yet it sometimes remains silent about a specific situation even though it is obligated according to the law to take action, which may lead to this silence or silence causing harm. For stakeholders arranges their administrative responsibility.In order to establish a balance between the public interest and the interest of individuals, the legislator intervened and decided that the administration’s silence and failure to respond or take an explicit position is tantamount to a negative administrative decision that may be challenged before the courts. Including what was stipulated in Article 2 of Law No. (88) of 1971 AD, regarding administrative judiciary: (The refusal or refusal of the administrative authorities to take a decision or action that they should have taken in accordance with the laws and regulations) is considered an administrative decision.Therefore, the negative administrative decision lies in the administration's refusal or abstention from taking a decision that it should have taken by law, and it is related to the actions issued by the administration while it exercises its restricted power.